Zonas susceptibles a inundaciones y elementos expuestos de la zona urbana de la parroquia Caracol, cantón Babahoyo, provincia de Los Ríos en el periodo septiembre – diciembre 2024 - Quispe Milán, Byron Bladimir (2025)
Due to the flash floods that occur in the Caracol parish, especially in winter due to the presence of heavy rainfall, the research work called "Areas susceptible to flooding and exposed elements of the urban area of the Caracol parish, Babahoyo canton, Los Ríos province in the period September-December 2024" was developed, which is aimed at determining the most vulnerable areas to the threat of flooding and the exposure of existing elements within the study site through the implementation of a hydrological-hydraulic model and the use of Geographic Information Systems (GIS) software to assess the risk of flooding in areas surrounding the banks of the Catarama River and its tributary, the Pijullo River. The research was based on a non-experimental study and the application of both analytical-descriptive methods and methods involving qualitative and quantitative aspects to detail the threat with real information and present reliable data. The results of hydraulic modeling in Iber, with peak flow estimates contrasted with numerical flow values associated with return times, were used to superimpose the hazard [draft, velocity] with critical-essential elements and thereby determine risk levels according to their exposure for the development of risk reduction measures. The primary conclusion is the need to implement flood mitigation strategies for the areas most prone to flooding, such as the outer parts of the parish, and reduce risk levels. Focusing on community resilience in disaster risk management issues.